Playing With a Stacked Deck: Why Was a Single Payer Plan Dealt Such Bad Cards? - Millard, Peter; Rosen, Clifford; Thomas, Susan (Maine Policy Review, 1996)
The final report of the Maine Health Care Reform Commission (MHCRC) was submitted to Governor Amgus King in November, 1995. Given the complexity of what we call the healthcare system as well as the moving targets of federal and state incentives for reform, the report accomplished a great deal in a short period of time. Commission members were "mandated to offer a single payer universal coverage bill, a multiple payer universal coverage bill, and a bill to achieve reform through incremental changes to the existing system, emphasizing cost containment, managed care, and improved access. The commission was also mandated to cost out its recommendations" Reactions to the MHCRC report were invited from individuals who represent constituencies which often have an influential role in healthcare. Five commentaries address pros and cons of particular elements of the commission’s report. This second commentary provides perspectives from three practicing physicians in Maine.